Reaction morphologies developed by nickel aluminides in type II hot corrosion conditions: The effect of chromium. (December 2015) - Gheno, Thomas; Zahiri Azar, Maryam; Heuer, Arthur H.; Gleeson, Brian
Highlights: NiAl is not prone to hot corrosion initially, but to localized internal oxidation. NiAlCr is unable to passivate and immediately undergoes uniform hot corrosion. Cr2 O3 kinetically facilitates NiO dissolution in Na2 SO4 . The gas p S O 3 is critical to the mode of attack. Abstract: The short-term reaction of Ni–36Al (at. %) and Ni–36Al–5Cr alloys with Na2 SO4 in O2 -0.1% SO2 at 700 °C was studied by SEM and TEM. Local failure of the protective scale on NiAl led to nodule development via internal oxidation. Conversely, NiAlCr underwent a uniform attack involving internal sulfidation, porous scale growth, and NiO and Al2 O3 dissolution into the sulfate. The roles of gas and sulfate compositions were studied by comparing exposures to Na2 SO4, Na2 SO4 –MgSO4 and Na2 SO4 –Cr2 O3 deposits in air and O2 -0.1% SO2 . The effect of Cr in preventing passivation during early-stage exposure was associated with a coupled dissolution of NiO and Cr2 O3 .